1983
DOI: 10.1126/science.6879193
|View full text |Cite
|
Sign up to set email alerts
|

Human Fetal Muscle and Cultured Myotubes Derived from It Contain a Fetal-Specific Myosin Light Chain

Abstract: Human fetal muscles at ages 110, 125, and 132 days contain a fetal-specific myosin light chain. This light chain is absent in adult human muscle, copurifies with myosin, and is identified as a slow light chain because it reacts with purified antibody to chicken slow muscle light chains and does not react strongly with antibody to fast myosin light chains. This light chain is synthesized in cultures of fetal muscle along with normal myosin light chains. The presence of a fetal light chain in culture provides a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…confirmed recently by Strohman et al (1983), that the two main light chains in human foetal myosin are those predominant in pure adult fast myosin, similar to other species (see Lowey et al, 1983). A minor light-chain component, specific to human foetal myosin, has also been identified and tentatively classified as a slow type of light chain (Strohman et al, 1983), possibly related to the LC1 light chain of human foetal or adult atrium and foetal ventricle (Cummins, 1983).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…confirmed recently by Strohman et al (1983), that the two main light chains in human foetal myosin are those predominant in pure adult fast myosin, similar to other species (see Lowey et al, 1983). A minor light-chain component, specific to human foetal myosin, has also been identified and tentatively classified as a slow type of light chain (Strohman et al, 1983), possibly related to the LC1 light chain of human foetal or adult atrium and foetal ventricle (Cummins, 1983).…”
mentioning
confidence: 67%
“…A minor light-chain component, specific to human foetal myosin, has also been identified and tentatively classified as a slow type of light chain (Strohman et al, 1983), possibly related to the LC1 light chain of human foetal or adult atrium and foetal ventricle (Cummins, 1983). We report here on the characterization of the heavy chains of human foetal and neonatal myosin by direct electrophoresis in SDS/polyacrylamide gels, peptide-mapping analysis and, as a complementary approach, by specific antibodies using e.l.i.s.a., and Western-blot immunoenzymicstaining techniques.…”
mentioning
confidence: 99%
“…Other multigene families which contain members coding for major muscle proteins have also been found to contain developmentally regulated isotypes. Thus, myosin light chain (28,32), myosin heavy chain (16), troponin I, T, and C (29), and tropomyosin (16) all possess fetal isoforms distinct from those found in adult muscle. It is notable that it is the embryonic form of these proteins which is expressed in cultured cells, even when they are derived from adult skeletal muscle (16,28,29,33;Blau,unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Such studies have produced the unexpected result that differentiating muscle cells from adult muscle do not express the same pattern of gene activity as the tissue from which they were derived. Instead, primary cells and myoblast cell lines derived from fetal or adult muscle exhibit a fetal pattern of myosin light chain (28,32), myosin heavy chain (33), troponin T, I, and C (29), and tropomyosin (16) syntheses. Recent studies support the existence of devel-* Corresponding author.…”
mentioning
confidence: 99%
“…The observed induction of many of the genes associated with muscle differentiation is most likely a consequence of Myogenin and MyoD expression. Of interest, Myl4, a fetal muscle gene that is absent from adult muscle (25) was also identified in our previous study of ARMS using human cDNA microarrays in which we found MYL4 expression in all seven ARMS cell lines tested (15).…”
Section: Induction Of a Myogenic Transcription Program By Pax3-fkhrmentioning
confidence: 99%